Exercise training in patients with corrected tetralogy of Fallot: A protocol for systematic review and meta-analysis. Issue 21 (28th May 2021) - Gong, Ya-Qin; Liu, Xiao-Yan; Zhi, Ping; Wei, Li-Na; Guo, Fang-Fei; Qian, Jin-Zhi; Wang, Yun-Xia; Dong, He-Li
Abstract: Background: The arrival of transcatheter mitral valve therapies has provided feasible and safe alternatives to medical and surgical treatments for mitral regurgitation. The aim of this study is to estimate the relative efficacy and safety of exercise training in patients with corrected tetralogy of Fallot through meta-analysis. Methods: : A systematic search will be performed using PubMed, EMBASE, the Cochrane Library, Web of Science, CBM, CNKI, WanFang Data, and VIP to include random controlled trials or nonrandom controlled trials comparing the efficacy and safety of exercise training in corrected tetralogy of Fallot patients. The risk of bias for the included nonrandom controlled studies will be evaluated according to Risk of Bias in Nonrandomized Studies of Interventions. We will use the Cochrane Collaboration's tool (version 2 of the Cochrane risk of bias tool for randomized trials) to assess risk of bias of included random controlled trials. Revman 5.4 and STATA 15.0 will be used to complete the meta-analysis and generate forest plots. Grading of recommendations assessment, development, and evaluation will be used to assess the quality of evidence. Results: : The results of this systematic review and meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: : This study will provide broad evidence of efficacy and safety of exercise training in patients with corrected tetralogy of Fallot and provide suggestions for clinical practice and future research. Protocol registration number: INPLASY202150006. Abstract : Supplemental Digital Content is available in the text